PERJANJIAN KERJASAMA ANTARA APOTEKER DENGAN PEMILIK APOTEK - Wirjanta, I Made; Putra Atmaja, Ida Bagus; Sri Indrawati, Anak Agung (Kertha Semaya : Journal Ilmu Hukum; Vol. 01, No. 11, November 2013)
A cooperation agreement which was carried out by the pharmacist with pharmacy owner have the goal to provide pharmaceutical activities for consumers or patients. In a cooperation agreement between pharmacists and pharmacist owner would have incurred a liability as well as the impact of arising in that agreement. Therefore, this paper will explain how the responsibilities arising from the cooperation agreement between the owner of pharmacist and pharmacist how settlement against the drift toward such cooperation agreement so that it can realize the maximum pharmaceutical activities service for the health of the consumer or patient.
Keywords: Agreement, Pharmacist, The Owner of Pharmacist, Consumer.